Economic effects of transportation infrastructure quantity and quality: A study of German counties - Dennis Gaus; Heike Link (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
In this paper, we analyze the impact of transportation infrastructure quantity and quality on regional economic production. We exploit an extensive panel dataset on the German county level (N=401), expressing the capital value and condition of highways between 2007 and 2016, to estimate a spatially extended translog production function. The spatial specification uses SLX and SDEM models, with various linear and nonlinear variants estimated using FGLS and GMM estimators accounting for endogeneity. We find, in line with existing research, a positive impact of the quantity of transport infrastructure both locally and supra-regionally. We furthermore provide evidence for the claim that insufficient maintenance and low infrastructure conditions significantly slow economic growth through a negative correlation between GDP and the quality grade of highways. A more detailed analysis, distinguishing different types of highways and constructions, confirms these findings and underlines the importance of the Bundesstraßen network as compared to the Autobahn system. The estimated impact of the quality of bridges is rather ambiguous and requires further research to achieve a better understanding.
Keywords: O18; R12; R42; 330; Transport; Infrastructure; Public Capital; Economic Growth; Regional Development